(untitled) - Schaefer, Richard T. (Boston, 2006)
The book provides a concise presentation of sociological theory and research. This text presents all the essentials of sociology, with illustrative examples, in a form that condenses lengthy, descriptive material. Some of its additional features include: a social policy section which illustrates applications of sociological issues to modern life by linking concepts, theories and research to newspaper headlines; three critical questions at the end of each chapter; contemporary and cross-cultural examples which are used throughout the text to explain sociological theories and concepts; and integrated coverage of issues affecting women
Keywords: Sociology